Metal glass composite
By adjusting the thermal expansion coefficient of glass powder and incorporating specific components, the metal-glass composite addresses adhesion and impact resistance issues, enhancing durability through controlled bubble suppression and matched thermal expansion.
Patent Information
- Application Number
- JP2023110338
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2043-07-04
AI Technical Summary
The challenge in forming a glassy coating on a metal base material through thermal spraying lies in the mismatch of thermal expansion coefficients between the metal and glass materials, leading to poor adhesion, air bubbles, and reduced impact resistance due to volumetric shrinkage differences.
A metal-glass composite is developed by adjusting the thermal expansion coefficient of the glass powder to match the metal base material, using specific compositions of SiO2, B2O3, Li2O, Na2O, BaO, TiO2, Al2O3, and ZnO to suppress air bubbles and enhance adhesion, with a molten solidified portion forming between the metal and glass layers.
The composite achieves improved impact resistance and adhesion by controlling thermal expansion and minimizing air bubbles, resulting in a durable and strong metal-glass interface.
Smart Images

Figure 2025008296000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a metallic glass composite, and more particularly to a metallic glass composite in which glass particles are thermally sprayed onto a metal surface and firmly adhered thereto. [Background technology]
[0002] Thermal spraying is used to form a glassy coating on a metal substrate. When a coating is formed by spraying a glassy material onto a metal substrate, the glassy material adheres to the metal substrate more firmly than enamel, forming a coating. Therefore, thermal spraying is suitable for products that require durability.
[0003] In a thermal spraying device, a carrier gas is mixed with a material to be sprayed, such as glass or ceramics. A separately supplied gas and a high current generate plasma, which becomes hot and melts the sprayed glass powder, which is made of glass particles. The molten sprayed glass powder is then ejected from the thermal spraying device toward the metal substrate to be sprayed (see Patent Documents 1 and 2, etc.).
[0004] The thermal expansion coefficient (linear expansion coefficient) of the metal substrate and the glassy material of the sprayed glass powder is different. Due to the specific heat relationship, the metal substrate cools faster. Since the rate of volumetric contraction differs between the metal substrate and the sprayed glass powder, control of the expansion coefficient is required, making spraying between dissimilar materials extremely difficult.
[0005] The inventors developed the sprayed glass powder and spraying method disclosed in Patent Document 1, and the spraying device disclosed in Patent Document 2. The inventors established strong spraying between dissimilar materials, a metal substrate and the glassy substance of the sprayed glass powder, and produced a metal glass composite. According to the disclosure of Patent Document 1, the surface of the metal substrate to be sprayed is roughened by sandblasting or the like and then heated. Then, a coating of glassy substance derived from the sprayed glass powder melted by spraying is formed on the surface. It is believed that the glassy substance derived from the sprayed glass powder penetrates into the surface of the metal substrate thus roughened, improving the adhesion between the metal substrate and the glassy substance. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2013-216977 A [Patent Document 2] JP 2021-130841 A Summary of the Invention [Problem to be solved by the invention]
[0007] The inventor then conducted extensive research into the formation of glass by thermal spraying on the surface of a metal substrate. The inventor discovered that it was necessary to adjust the thermal expansion coefficient of the sprayed glass powder according to the type of metal substrate, since the thermal expansion coefficient differs depending on the type of metal substrate. The inventor also discovered that bubbles inevitably occur when the sprayed glass powder is melted by thermal spraying and applied to the metal substrate, which reduces the impact resistance of the glass in the resulting metallic glass composite.
[0008] The present invention has been made in consideration of the above-mentioned points, and provides a metallic glass composite in which a metal substrate and a glassy dissimilar material, a thermal spray glass powder, are integrated by thermal spraying. The thermal spray glass powder has a thermal expansion coefficient corresponding to the metal substrate to be thermal sprayed, and air bubbles contained in the glass formed on the metal substrate after thermal spraying are suppressed, thereby improving strength such as impact resistance. [Means for solving the problem]
[0009] That is, the metallic glass composite of the embodiment has a metal substrate made of a body-centered cubic iron material, and a sprayed glass portion formed on the metal substrate with a film thickness of 10 to 2000 μm. The glass material forming the sprayed glass portion is a first group component (A) containing 35 to 70 mass% of SiO2, and a second group component (B) containing 9 to 15 mass% of B2O3, 5 to 9 mass% of Li2O, and 4 to 10 mass% of Na2O. The glass material has a linear expansion coefficient of 9 to 11 (×10) at room temperature to 300° C., and the glass material has a linear expansion coefficient of 9 to 11 (×10) at room temperature to 300° C., and the glass material has a linear expansion coefficient of 9 to 11 (×10) at room temperature to 300° C., and the glass material has a linear expansion coefficient of 9 to 11 (×10) at room temperature to 300° C., and the glass material has a linear expansion coefficient of 9 to 30 ... 6 / °C), and the area ratio of bubbles of 1 µm or more in the cross section in the thickness direction of the sprayed glass portion is less than 40%.
[0010] The metallic glass composite of the embodiment has a metal substrate made of a face-centered cubic iron material and a sprayed glass portion formed on the metal substrate with a film thickness of 10 to 2000 μm. The glass material forming the sprayed glass portion is a first group component (A) of SiO2: 50 to 60 mass%, a second group component (B) of B2O3: 2 to 8 mass%, Li2O: 8 to 15 mass%, and Na2O: 8 to 20 mass%, totaling 2. The glass material has a linear expansion coefficient of 14 to 17(×10) at room temperature to 300° C., and a glass material having a linear expansion coefficient of 14 to 17(×10) at room temperature to 300° C., and a glass material having a linear expansion coefficient of 14 to 35 ... 6 / °C), and the area ratio of bubbles of 1 µm or more in the cross section in the thickness direction of the sprayed glass portion is less than 40%.
[0011] Furthermore, the difference between the linear expansion coefficient of the glass material of the metallic glass composite and the linear expansion coefficient of the metal substrate may be within 15%.
[0012] Furthermore, the metallic glass composite may have a molten and solidified portion in which the sprayed glass portion is embedded in the metal substrate portion at the boundary between the metal substrate portion and the sprayed glass portion in the cross section, and the molten and solidified portion may have a thickness of 0.3 μm or more.
[0013] Furthermore, the sprayed glass portion of the metallic glass composite may have an area ratio of 1 μm or larger bubbles that exist within an area of 30% of the thickness of the sprayed glass portion starting from the boundary between the metal substrate portion and the sprayed glass portion in the cross section, of 50% or less.
[0014] Furthermore, the thickness of the sprayed glass portion of the metallic glass composite may be 10 to 100 μm, and the area ratio of bubbles of 1 μm or more in the cross section in the thickness direction of the sprayed glass portion may be less than 10%.
[0015] Furthermore, the components of the metallic glass composite other than the main component (D) of the glass material are auxiliary components (E), which are CaO, SrO, MgO, P2O5, K2O, V2O5, Cr2O3, MnO2, Fe2O3, Co3O4, NiO2, CuO, Y2O3, ZrO2, Nb2O2, MoO3, SnO2, Sb2O3, WO3, PbO, Bi2O3, La2O3, CeO2, Pr6O 11 , Nd2O3, Sm2O3, and Gd2O3 may be used as the oxide. Effect of the Invention
[0016] The metallic glass composite of the present invention is a metallic glass composite in which a metal substrate and a glassy dissimilar material, a thermal spray glass powder, are integrated by thermal spraying. The thermal spray glass powder can be prepared to have a thermal expansion coefficient corresponding to the metal substrate to be thermal sprayed, and air bubbles contained in the glass formed on the metal substrate after thermal spraying can be suppressed, thereby increasing strength such as impact resistance. [Brief description of the drawings]
[0017] [Figure 1]FIG. 1 is a schematic cross-sectional view of a metallic glass composite of (A) a plate material, (B) a perforated plate material, (C) a tube material, and (D) a bolt material; and (E) a schematic diagram showing the compositional relationship of the glass materials. [Diagram 2] FIG. 2A is a schematic diagram showing the compositional relationship of glass materials, and FIG. 2B is a schematic cross-sectional view showing the structure of a metallic glass composite. [Diagram 3] 1A is a cross-sectional photograph enlarged at 100 times, and (B) is a cross-sectional photograph enlarged at 1000 times, of the metallic glass composite of prototype number G1. [Figure 4] 1A and 1B are cross-sectional photographs enlarged 100 and 1,000 times, respectively, of the metallic glass composite of prototype number G2. [Diagram 5] 1A is a 100x magnified cross-sectional photograph of the glass material of the metallic glass composite of prototype sample number G6, and (B) is a 1000x magnified cross-sectional photograph. [Figure 6] 1A is a 100x magnified cross-sectional photograph of the glass material of the metallic glass composite of prototype sample number G11, and (B) is a 1000x magnified cross-sectional photograph. [Figure 7] 1A is a 100x magnified cross-sectional photograph of the glass material of the metallic glass composite of prototype sample number G13, and (B) is a 1000x magnified cross-sectional photograph. [Figure 8] 1A is a 100x magnified cross-sectional photograph of the glass material of the metallic glass composite of prototype sample number G19, and (B) is a 1000x magnified cross-sectional photograph. [Figure 9] 1A is a 100x magnified cross-sectional photograph of the glass material of the metallic glass composite of prototype sample number H5, and (B) is a 1000x magnified cross-sectional photograph. [Figure 10] 1 is a graph showing the relationship between the area ratio of all bubbles and the height of a falling ball. [Figure 11] 1 is a graph showing the relationship between the area ratio of bubbles in a boundary portion and dielectric strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The metal glass composite of the embodiment is a metal-glass composite in which a glassy coating is formed on the entire or part of the surface of various types of metal by thermal spraying. The glassy material is prepared in a powder form such as frit and is supplied to a thermal spraying device. The glassy powder is instantaneously melted by plasma spraying of the thermal spraying device and sprayed toward the target metal substrate. As a result, the molten glassy material is deposited on the metal substrate and cooled, and the glassy material is fixed to the metal and integrated.
[0019] 1A to 1D are schematic diagrams of metallic glass composites 1A, 1B, 1C and 1D in which a sprayed glass portion 20 is formed on (on) a metal substrate portion 10. FIG.
[0020] FIG. 1(A) shows a metallic glass composite 1A in which a sprayed glass portion 20 is formed on the surface of a sheet metal-like metal substrate 11 (10). The sprayed glass portion 20 is formed on the surface of a metal substrate 11 such as a steel plate by spraying. As a result, the impact resistance, corrosion resistance, etc. of a steel plate are imparted. FIG. 1(B) shows a metallic glass composite 1B in which a sheet metal-like metal substrate 12 (10) having a hole portion 15 for fixing with a bolt, rivet, etc., and connecting other members is prepared, and the sprayed glass portion 20 is formed on the surface of the metal substrate 12. The sprayed glass portion 20 is attached to the hole portion 15 and the periphery of the hole portion 15, so that resistance to abrasion, corrosion, etc. due to contact between metals can be improved.
[0021] FIG. 1(C) shows a metallic glass composite 1C in which a sprayed glass portion 20 is formed on the surface of a metal substrate portion 13(10) of a pipe material. In the case of the metallic glass composite 1C, it is possible to form an electrode for silent discharge by combining with another cylindrical electrode (see Patent Document 1, etc.). The insulating performance due to the glass quality of the sprayed glass portion 20 is utilized. In FIG. 1(D), a bolt is used as the metallic substrate portion 14(10). By forming the sprayed glass portion 20 on the surface of the bolt, the corrosion resistance of the bolt is improved, and the resistance to the bolt breaking due to weakening caused by corrosion is increased. Of course, the metallic glass composite disclosed in FIG. 1 is a so-called example, and the metallic glass composite is not limited to the illustrated embodiment.
[0022] In the metal glass composite of the embodiment, the thickness of the sprayed glass part 20 is in the range of 10 to 2000 μm. If the thickness of the sprayed glass part 20 is less than 10 μm, the molten glass material is likely to be striped or spotted on the surface of the metal substrate part 10. Therefore, it is likely to be difficult to homogenize the deposition of the glass material. In addition, if the thickness of the sprayed glass part 20 exceeds 2000 μm, the thickness of the sprayed glass part 20 becomes too large, and cracks and peeling are likely to occur due to the difference in thermal expansion coefficient between the metal substrate part 10 and the sprayed glass part 20. In particular, it becomes more difficult to control the bubbles contained in the sprayed glass part 20 as described later.
[0023] In preparing the metallic glass composite of the embodiment, the composition of the glass material constituting the sprayed glass portion is determined by the difference in thermal expansion coefficient (linear expansion coefficient) due to the type of metal in the metal substrate, particularly the type of iron material (iron alloy). The metallic glass composite of the embodiment mainly uses a body-centered cubic iron material and a face-centered cubic iron material as the metal substrate.
[0024] The body-centered cubic iron material is a martensitic stainless steel, a ferritic stainless steel, etc., such as stainless steels SUS409, SUS420, SUS430, etc., and general structural rolled steels such as SS400. In the examples described below, SUS409 and SS400 are used. The face-centered cubic iron material is an austenitic stainless steel, etc., such as SUS304, SUS310, SUS316, etc. In the examples described below, SUS304 is used.
[0025] In order to correspond to the metal type of the metal substrate, it is necessary to adjust the composition of the glass material constituting the sprayed glass part. The schematic diagram of FIG. 2(A) shows an overview of the composition of the glass material constituting the sprayed glass part. First, the main component (D) is composed of the first group component (A), the second group component (B), and the third group component (C). In the glass material per unit weight, the main component (D) is 90 mass% or more. Then, the auxiliary component (E) is mixed as the remaining component of the glass material. Of course, it is possible that an unavoidable impurity component is mixed into the glass material. Hereinafter, mass% and weight% are treated as synonyms. The mass% ratio between the first group component (A), the second group component (B), and the third group component (C) varies depending mainly on the body-centered cubic iron material or the face-centered cubic iron material.
[0026] The first group component (A) is SiO2. The SiO2 of the first group component (A) constitutes the main component of the glass material that constitutes the sprayed glass part, and mainly increases the corrosion resistance, hardness (abrasion resistance), antifouling properties, electrical insulation, voltage resistance, etc. In the case of a metal substrate made of a body-centered cubic iron material, the compounding ratio in the glass material is 35 to 70 mass%. In addition, in the case of a metal substrate made of a face-centered cubic iron material, the compounding ratio in the glass material is 50 to 60 mass%.
[0027] If the blending ratio of SiO2 in the first group component (A) is below the respective lower limits, the properties such as corrosion resistance of the final sprayed glass part are reduced. In addition, the sprayed glass part is more likely to undergo changes over time such as whitening. If the blending ratio of SiO2 in the first group component (A) is above the respective upper limits, the surface of the sprayed glass part formed after spraying is less likely to be flat. During spraying, the metal substrate to be sprayed is heated to a temperature above the heat distortion temperature (1000°C or higher). As the amount of SiO2 increases, the fire resistance of the glass material itself increases, and the melting property during plasma spraying decreases. As a result, the load on the spraying device increases and it becomes difficult to obtain smoothness of the sprayed glass part after melting.
[0028] The thermal expansion coefficient of SiO2 is smaller than that of each of the following components. An increase in the amount of SiO2 reduces the thermal expansion coefficient of the entire glass material. In addition, the melting property during plasma spraying is low and the viscosity is high. Therefore, SiO2 is selected from the viewpoints of adjusting the thermal expansion coefficient of the metal substrate of the body-centered cubic iron material or the face-centered cubic iron material, as well as corrosion resistance and ease of spraying and melting. The amount of SiO2 in the glass material is determined according to the composition of the metal substrate, taking into account the adjustment of the thermal expansion coefficient.
[0029] The second group component (B) is a component that mainly adjusts the melting property and low viscosity of the glass material when melted, and includes B2O3, Li2O, and Na2O. The total amount of the second group component (B) and the amount of each component included in the second group component (B) are adjusted and mixed in order to bring the thermal expansion coefficient of the glass material closer to that of the metal substrate.
[0030] B2O3 promotes the melting property and low viscosity of glass material during plasma spraying. Therefore, it is essential for adjusting the action of SiO2 and other components. The thermal expansion coefficient of B2O3 is small, just like SiO2. However, contrary to SiO2, B2O3 reduces corrosion resistance, hardness (abrasion resistance), electrical insulation, and voltage resistance, and promotes changes over time. For this reason, an increase in the amount of B2O3 impairs the properties of the sprayed glass part. B2O3 is easily volatilized by heating during spraying, and it is not easy to control the amount of volatilization. As B2O3 volatilizes, the thermal expansion coefficient of the glass material at the time of the initial design changes.
[0031] In the case of a metal substrate made of a body-centered cubic iron material, the glass material contains 9 to 15% by mass of B2O3. In the case of a metal substrate made of a face-centered cubic iron material, the glass material contains 2 to 8% by mass of B2O3. If the B2O3 content exceeds the upper limit, the glass coating of the sprayed glass part formed on the surface of the metal substrate is likely to peel off or crack (crack). If the B2O3 content falls below the lower limit, the glass material does not fully melt and has low viscosity during plasma spraying, making it impossible to obtain a suitable glass material.
[0032] Li2O is an essential component for adjusting the action of SiO2 and other components, as it promotes the melting property and low viscosity of the glass material during plasma spraying. At the same time, Li2O is relatively difficult to volatilize during plasma spraying, and has the largest thermal expansion coefficient compared to other components. For this reason, Li2O acts as a buffer material in adjusting the thermal expansion coefficient of other components and expressing the properties of the glassy coating of the desired sprayed glass part. Li2O reduces the corrosion resistance and hardness (abrasion resistance) against acids and alkalis. Then, the glass material during spraying is more likely to recrystallize (lithium silicate crystallization). Although the corrosion resistance etc. improves with recrystallization, the thermal expansion coefficient of the glassy coating that is completed by recrystallization decreases. This decrease in the thermal expansion coefficient is difficult to control, and ultimately causes penetration (cracks) in the surface of the coated object.
[0033] In the case of a metal substrate made of body-centered cubic iron material, the Li2O content in the glass material is 5 to 9 mass%. In the case of a metal substrate made of face-centered cubic iron material, the Li2O content in the glass material is 8 to 15 mass%. If the Li2O content exceeds the upper limit, in addition to the above-mentioned problems such as peeling, the deterioration of electrical insulation, voltage resistance, corrosion resistance, etc. becomes prominent. If the Li2O content is below the lower limit, the melting property and low viscosity during plasma spraying are not achieved.
[0034] Depending on the amount of Na2O in the glass material, Na2O increases the melting property of the glass material during plasma spraying, and at the same time increases the viscosity during melting. As a result, the glass material sprayed on the surface of the metal substrate to be sprayed becomes more easily attached to the surface of the metal substrate, and the adhesive strength between the sprayed glass portion and the surface of the metal substrate is increased. In addition, the fluidity of the molten glass material itself attached to the surface of the metal substrate decreases somewhat due to the increase in viscosity of the glass material caused by Na2O, so that the movement of bubbles caught in the spraying (bubbles gathering together and becoming larger due to fluidity) is also suppressed (see the examples described later). Na2O greatly contributes to improving the smoothness of the sprayed glass portion after plasma spraying and reducing its film thickness, and also increases the electrical insulation and voltage resistance. In addition, Na2O enhances electrical insulation and voltage resistance when it is at the same mass ratio (weight ratio) as Li2O, and is also excellent in terms of functionality.
[0035] Since the thermal expansion coefficient of Na2O is the second largest after Li2O, it is easy to design the thermal expansion coefficient of the glass material according to the thermal expansion coefficient of the metal substrate of the body-centered cubic iron material to be sprayed or the material of the individual metal substrate of the face-centered cubic iron material. In this case, the amount of Na2O added depends on the amount ratio with Li2O. Furthermore, it is worth noting that the viscosity at the time of melting expressed by the addition of Na2O has different properties from the viscosity at the time of melting expressed by the addition of Al2O3 and CaO, which will be described later. In the case of Na2O, the viscosity at the time of melting tends to increase almost linearly as the amount of Na2O added increases. On the other hand, in the case of Al2O3 and CaO, the viscosity at the time of melting changes suddenly depending on the amount of Al2O3 and CaO added. For this reason, Na2O is suitable for ease of viscosity control when melting glassy materials.
[0036] However, Na2O, like B2O3, is easily volatilized by plasma spraying, and the amount of volatilization is greater than that of Li2O. The thermal expansion coefficient of Na2O is significantly different from that of B2O3. Therefore, in the case of a metal substrate made of body-centered cubic iron material, the glass material contains 4 to 10 mass% of Na2O. In addition, in the case of a metal substrate made of face-centered cubic iron material, the glass material contains 8 to 20 mass% of Na2O.
[0037] The upper limit of the blending ratio of Na2O is a range that takes into consideration the thermal expansion coefficient of the material of the metal substrate part of the body-centered cubic iron material to be sprayed, or the material of the individual metal substrate part of the metal substrate part of the face-centered cubic iron material. In particular, when the blending ratio of Na2O is 20 mass% or more, the composition of the sprayed glass part itself after spraying changes significantly due to the volatilization of Na2O, which may cause the sprayed glass part to peel off or crack from the surface of the metal substrate part. In addition, the glass material melts and becomes thread-like in the spraying device described later, which inhibits uniform spraying. In addition, in the case of a sprayed glass part formed from a glass material containing a large amount of Na2O, the corrosion resistance and hardness (wear resistance) are likely to decrease. Note that, when the blending ratio of Na2O is below the lower limit, the characteristic of increasing the meltability of the glass material and increasing the viscosity during melting at the same time is not observed, and the desired electrical insulation and voltage resistance cannot be obtained.
[0038] Each of the components B2O3, Li2O, and Na2O included in the second group component (B) is a component that is relatively easy to volatilize when the glass material is heated in plasma spraying. When a sprayed glass part derived from the molten glass material is formed on the surface of the metal substrate, the entrapment of air bubbles is unavoidable. Therefore, as the characteristics of the glass material used in the metal glass composite of the embodiment, it is required to utilize the function due to the second group component (B), to converge to a composition of the glass material considering the thermal expansion coefficient of the material of the metal substrate, and to suppress the amount of air bubbles generated in the sprayed glass part. If the amount of air bubbles in the sprayed glass part is excessive, the density of the sprayed glass part itself is lost, which is likely to lead to partial strength reduction. In addition, dielectric breakdown is likely to occur due to the variation in the dielectric constant of the sprayed glass part.
[0039] Therefore, in the glass material used in the metallic glass composite of the embodiment, when the second group component (B) is lumped together, in the case of a metal substrate made of a body-centered cubic iron material, the second group component (B) is blended in a total amount of 18 to 30 mass% in the glass material, and in the case of a metal substrate made of a face-centered cubic iron material, the second group component (B) is blended in a total amount of 25 to 35 mass% in the glass material.
[0040] The third group component (C) is a component that is blended mainly for the purpose of assisting in the formation of glass in the sprayed glass portion that occurs after thermal spraying, etc. The third group component (C) includes BaO, TiO2, Al2O3, and ZnO.
[0041] BaO is a component that assists the glass formation of SiO2 in glass materials. The more BaO is added, the more the glass material melts and the lower the softening temperature of the glass material during spraying. Although the effect is less than the increase in viscosity caused by Na2O, the addition of BaO increases the adhesion strength of the glass material sprayed on the surface of the metal substrate. For this reason, BaO improves the smoothness of the glass coating of the sprayed glass part formed after plasma spraying. Therefore, BaO contributes to reducing the film thickness of the sprayed glass part, and in addition, increases the electrical insulation, voltage resistance, and dielectric constant of the sprayed glass part. When BaO is added in the same amount as alkaline components such as Li2O and Na2O, it is superior to Li2O, Na2O, etc. in electrical insulation and voltage resistance.
[0042] Therefore, in the case of a metal substrate made of a body-centered cubic iron material, BaO is mixed in the glass material at 0 to 15% by mass. In the case of a metal substrate made of a face-centered cubic iron material, BaO is mixed in the glass material at 3 to 12% by mass. If the mixing ratio of BaO in the glass material exceeds the upper limit, the viscosity of the glass of the sprayed glass part when the glass material is plasma sprayed becomes extremely high. As a result, the molten glass material melts in a spraying device described later and becomes thread-like, hindering uniform spraying. In the coating of the sprayed glass part formed after spraying, the corrosion resistance and the like are reduced and it becomes brittle to changes over time. In the case of a metal substrate made of a body-centered cubic iron material, the lower limit of the mixing ratio of BaO may be zero (0% by mass). Preferably, the lower limit of the mixing ratio of BaO is 3% by mass, similar to the metal substrate made of a face-centered cubic iron material. Although it depends on the amounts of other components, this is because it takes into consideration improvements in the electrical insulation, voltage resistance, dielectric constant, etc. of the formed sprayed glass part, and improvements in the adhesive strength of the glass coating on the surface of the substrate.
[0043] TiO2 is a component that assists in the glass formation of SiO2 in glass materials. The more TiO2 is added, the more the hardness (abrasion resistance) of the glass coating of the sprayed glass portion formed increases. TiO2 also improves corrosion resistance, electrical insulation, and voltage resistance. TiO2 increases the viscosity of the glass material after spraying. Therefore, in the case of a metal substrate made of body-centered cubic iron material, TiO2 is added in an amount of 2 to 15 mass% in the glass material. In addition, in the case of a metal substrate made of face-centered cubic iron material, TiO2 is added in an amount of 4 to 15 mass% in the glass material.
[0044] If the TiO2 content exceeds the upper limit, crystallization of the glass occurs when the glass material molten by the heating of the plasma spray cools (slowly cools) to become the sprayed glass part. In other words, the thermal expansion coefficient becomes smaller, making it easier to induce peeling. Crystallization of the glass drastically reduces hardness, corrosion resistance, etc. If the TiO2 content falls below the lower limit, it becomes difficult to improve the electrical insulation, voltage resistance, dielectric constant, etc. of the sprayed glass part formed, and to achieve meltability during melting of the plasma spray, although this depends on the amounts of other components.
[0045] Al2O3 is a component that assists the glass formation of SiO2 in the glass material. Al2O3 improves the corrosion resistance, hardness (abrasion resistance), electrical insulation, voltage resistance, etc. of the glass coating of the sprayed glass part formed by the molten glass material, and prevents recrystallization. It can be said that the incorporation of Al2O3 is desirable for improving the recrystallization of the glass of the sprayed glass part by containing Li2O. Therefore, in the case of a metal substrate part of a body-centered cubic iron material, Al2O3 is incorporated in the glass material at 0 to 8 mass%. In addition, in the case of a metal substrate part of a face-centered cubic iron material, Al2O3 is incorporated in the glass material at 0 to 5 mass%. If the incorporation ratio of Al2O3 exceeds the upper limit, the melting property of the glass material during plasma spraying is reduced and the viscosity is extremely increased. The lower limit of the incorporation ratio of Al2O3 may be no incorporation (0 mass%), and is preferably 2 mass%. The inclusion of Al2O3 improves the corrosion resistance of the sprayed glass part and prevents recrystallization.
[0046] ZnO is a component that assists the glass formation of SiO2 in glass materials. As with BaO, the more ZnO is added, the more the glass material melts and the lower the softening temperature of the glass material during spraying. Although the effect is less than the increase in viscosity caused by Na2O, the addition of ZnO increases the adhesion strength of the sprayed glass part sprayed on the surface of the metal substrate. For this reason, like BaO, ZnO improves the smoothness of the glass coating of the sprayed glass part formed after plasma spraying and contributes to reducing the thickness of the glass coating of the sprayed glass part. In addition, the electrical insulation, voltage resistance, and dielectric constant of the glass of the sprayed glass part are improved. If ZnO is added in the same amount as alkaline components such as Li2O and Na2O, it is superior to Li2O, Na2O, etc. in electrical insulation and voltage resistance.
[0047] In the case of a metal substrate made of a body-centered cubic iron material, ZnO is blended in the glass material at 0 to 15% by mass. In the case of a metal substrate made of a face-centered cubic iron material, ZnO is blended in the glass material at 0 to 5% by mass. If the blending ratio of ZnO exceeds the upper limit, the viscosity of the molten glass material when plasma spraying the glass material increases. As a result, the molten glass material melts in a spraying device described later and becomes thread-like, hindering uniform spraying. Even in the case of the glassy material of the sprayed glass part formed after spraying, crystallization of the glassy material is caused, so that the thermal expansion coefficient is reduced and peeling may be induced. As a result, the corrosion resistance of the glassy coating of the sprayed glass part is reduced and it becomes fragile with time. In particular, the crystallization of the glassy material cannot be controlled. The lower limit of the blending ratio of ZnO may be no blending (0% by mass) regardless of whether the metal substrate is made of a body-centered cubic iron material or a face-centered cubic iron material. It is preferably 2% by mass. Depending on the amounts of other components blended, this tends to contribute to improving the electrical insulation properties, voltage resistance, dielectric constant, etc. of the glassy material in the sprayed glass part formed after thermal spraying, and to improving the adhesion strength of the glassy material on the surface of the substrate.
[0048] The third group component (C) is intended to improve the performance of the glass quality of the sprayed glass portion generated after thermal spraying. For this reason, depending on the application, function, etc. of the metallic glass composite, it is permitted not to mix any of the components included in the third group component (C) as described above. In addition, the mixing ratio of the third group component (C) is adjusted depending on the balance with the first group component (A) and the second group component (B) and the adjustment of the thermal expansion coefficient. For this reason, in the glass material used in the metallic glass composite of the embodiment, when the third group component (C) is lumped together, in the case of a metal substrate part made of a body-centered cubic iron material, the third group component (C) is mixed in a total of 10 to 30 mass% in the glass material. In addition, in the case of a metal substrate part made of a face-centered cubic iron material, the third group component (C) is mixed in a total of 10 to 20 mass% in the glass material.
[0049] In the glass material used in the metallic glass composite of the embodiment, the main component (D) is the total blend of the first group component (A), the second group component (B), and the third group component (C). The blending ratio of the main component (D) in the glass material is 90 mass% or more. The entire glass material can be made of only the main component (D), except for impurities that are inevitably mixed in. Furthermore, in consideration of the application and durability of the metallic glass composite, an auxiliary component (E) is further blended with the main component (D).
[0050] The auxiliary component (E) is blended in the glass material composed of the oxide species of the main component (D) described above for the purposes of facilitating thermal spraying, improving the glass quality when the glass material is melted, and stabilizing the properties of the glass coating of the thermal sprayed glass portion, and enhancing or adding functions. The auxiliary component (E) is contained in the glass material at 0 to 10 mass % for compositional balance. The compositional components included in the auxiliary component (E) are shown below by function.
[0051] CaO improves corrosion resistance, hardness (abrasion resistance), etc. CaO also increases the melting property of the glass material during thermal spraying and decreases the softening temperature of the glass material during thermal spraying. This increases the adhesion strength of the glass material sprayed onto the surface of the metal substrate. In the presence of BaO, a small amount of CaO improves the transparency of the glass coating of the sprayed glass part. Although this depends on the blending ratio with other alkaline components, if the amount of CaO is large, it reduces the corrosion resistance and hardness and also deteriorates the melting property during thermal spraying.
[0052] SrO increases the melting property of the glass material during thermal spraying and lowers the softening temperature of the glass material during thermal spraying. This increases the adhesion strength of the glass material sprayed onto the surface of the metal substrate. Although SrO does not volatilize easily during thermal spraying, adding a large amount of it induces crystallization during slow cooling of the sprayed glass part, which can cause peeling.
[0053] MgO, P2O5, K2O, V2O5, MnO2, Fe2O3, Co3O4, NiO2, CuO, MoO3, SnO2, PbO, BiO2, and Lu2O3 increase the melting property of the glass material during thermal spraying, and also lower the softening temperature of the glass material during thermal spraying. This increases the adhesion strength of the glass material sprayed onto the surface of the metal substrate. However, depending on the amount, corrosion resistance, hardness (abrasion resistance), electrical insulation, and voltage resistance may decrease, and the viscosity of the glass material during thermal spraying may suddenly increase.
[0054] Cr2O3, ZrO2, and WO3 increase the hardness (abrasion resistance) of the glass coating on the sprayed glass part. Of these, ZrO2 improves corrosion resistance, electrical insulation, and voltage resistance. Sb2O3 works to reduce and shrink the amount of bubbles in the glass material that is sprayed and adhered to the surface of the metal substrate. However, depending on the amount added, ZrO2 and Sb2O3 can suddenly increase the viscosity of the glass when melted.
[0055] Y2O3, Nb2O5, Ta2O3, Bi2O3, La2O3, CeO2, Pr6O 11Nd2O3, Sm2O3, and Gd2O3 improve the electrical insulation and voltage resistance of the sprayed glass part formed on the surface of the metal substrate. However, depending on the content, the melting temperature of the glass material increases, decreasing the melting property during spraying. In addition, they may cause a sudden increase in the viscosity of the glass material when melted.
[0056] The metallic glass composites 1A, 1B, 1C, and 1D disclosed in the schematic diagrams (A) to (D) of FIG. 1 are generally produced in the following order. First, a metal substrate to be sprayed is prepared. The surface of the metal substrate is then blasted. In the blasting, fine particles such as Al2O3 (alundum), SiC (carborundum), etc. are sprayed onto the surface of the metal substrate. The surface of the metal substrate is roughened by sandblasting, which enhances the thermal conduction to the metal substrate during heating, as described below. Note that the blasting is optional and is selected according to the shape of the metal substrate and the portion to be sprayed.
[0057] The surface temperature of the metal substrate is heated to 200 to 1000°C, preferably 500 to 1000°C, more preferably 700 to 1000°C. An electric furnace or the like is used for heating. The heating is performed to maintain the molten state of the glass material prior to the thermal spraying described below. If the metal substrate is at room temperature, the adhesion of the molten glass material to the metal substrate is extremely reduced.
[0058] For the thermal spraying, a plasma spraying device as described in Patent Document 2 and the like is used. The glass material is a glassy powder (frit) containing the above-mentioned compositional components. The glass material is supplied as a powder to a plasma spraying device, where it is instantaneously melted in the presence of a carrier gas, and sprayed onto the surface of a heated metal substrate to adhere to the surface. The amount of spraying onto the surface of the metal substrate and the number of sprays are adjusted to adjust the thickness of the glassy coating of the sprayed glass portion. In the examples described below, argon gas or dry air was used as the carrier gas.
[0059] The thickness of the glass coating on the sprayed glass portion can be set in a wide range, from 10 to 2000 μm. For example, in the case of a printing roll, the glass coating is set to a thickness of 1000 to 2000 μm. In the case of an electrode for silent discharge, the glass coating is set to a thickness of 300 to 1500 μm. Furthermore, in the case of a bolt, the glass coating is set to a thickness of 10 to 100 μm. Of course, these thicknesses are merely examples, and the thickness may be increased or decreased in consideration of the application, durability, etc.
[0060] After the spraying, the sprayed glass portion formed on the surface of the metal substrate is cooled slowly or air-cooled. Then, if necessary, the surface is polished, ground, or otherwise finished to be smooth. In this manner, the metallic glass composites 1A, 1B, 1C, 1D, etc. shown in the schematic diagrams (A) to (D) of FIG. 1 are produced.
[0061] In order to maintain a strong adhesion between the metal substrate and the sprayed glass portion, it is necessary to match the thermal expansion coefficients of the metal substrate and the sprayed glass portion as much as possible. As described above, both the metal substrate and the sprayed glass portion undergo volumetric shrinkage during cooling after spraying. However, due to the difference in expansion coefficients, the degree of volumetric shrinkage differs, resulting in poor adhesion such as gaps between the metal substrate and the sprayed glass portion or cracks in the sprayed glass portion.
[0062] For the metal substrate of body-centered cubic iron material, for example, the linear expansion coefficient of SUS409 is 9.9 (× 10 6 / ℃), and the linear expansion coefficient of SS400 is 12(×10 6 / ℃). Therefore, in order to make the glass material used for the sprayed glass part correspond to the linear expansion coefficient of the metal substrate of the body-centered cubic iron material, the linear expansion coefficient of the glass material from room temperature to 300℃ is set to 9 to 11 (×10 6 / ℃).
[0063] For the metal substrate of face-centered cubic iron material, for example, the linear expansion coefficient of SUS304 is 17.3(×10 6 / ℃). Therefore, in order to make the glass material used for the sprayed glass part correspond to the linear expansion coefficient of the metal substrate of the face-centered cubic iron material, the linear expansion coefficient of the glass material from room temperature to 300℃ is set to 14 to 17 (×10 6 / ℃).
[0064] When adjusting the thermal expansion coefficient of the metal substrate and the sprayed glass portion (glass material), in addition to the adjustment according to the type of metal substrate as described above, the difference in the linear expansion coefficient between the metal substrate and the sprayed glass portion (glass material) is adjusted to be as small as possible. Specifically, the difference between the linear expansion coefficient of the glass material and the linear expansion coefficient of the metal substrate is set to within 15%. In theory, it is possible to make the linear expansion coefficients of both completely match (the difference is 0%). However, in the case of a metal substrate having a curved surface or other shape, the contraction force of the sprayed glass portion formed after plasma spraying is utilized, and the sprayed glass portion can be more firmly attached to the surface of the metal substrate.
[0065] Metal glass composites according to the type of metal substrate are exemplified as follows. Examples of iron-based materials include conveyor rolls and rollers, and plywood for building materials. Examples of alloys (stainless steel-based materials) include water source rollers for printing equipment, bath rollers for zinc plating, various rolls and rollers used at room temperature, various rolls and rollers for heating furnaces, electrodes for silent dischargers that generate ozone, and electrodes for generating plasma. Examples of nickel alloys include metal setters for firing various sintered bodies. Examples of chromium-molybdenum steel alloys (e.g., SCM435, etc.) include vehicle bolts (especially for fastening dissimilar metals, and for fastening parts that generate sparks due to friction and static electricity), bolts for fastening various wind power generation parts (especially bolts for fastening offshore wind power generation), and bolts for general machinery and equipment.
[0066] In the metallic glass composite of the embodiment, as shown in the cross-sectional schematic diagram of FIG. 2(B), a molten solidified portion 40 is formed in which the sprayed glass portion is embedded in the metal substrate portion at a boundary portion 30 between the metal substrate portion 10 and the sprayed glass portion 20 in the cross section. The molten solidified portion 40 is formed to a thickness of 0.3 μm or more. Air bubbles 21 exist in the sprayed glass portion 20, and residual glass material 22 exists in the metal substrate portion 10 of the molten solidified portion 40. The symbol T30 in the figure is a mark indicating a 30% area in the thickness direction of the sprayed glass portion 20 starting from the boundary portion 30.
[0067] A notable phenomenon in the metallic glass composite of the embodiment is that the molten glass material sprayed onto the metal substrate is not simply deposited (deposited) on the surface of the metal substrate. Specifically, it was confirmed by observation with a scanning electron microscope (SEM) that the heated metal substrate and the molten glass material are mixed together at the surface layer (the boundary between the two) of the metal substrate, and some of the molten glass material penetrates into the metal substrate (see the electron microscope photographs in FIG. 3 and subsequent figures). As a result, after cooling, a molten solidified portion is generated in which the sprayed glass portion is embedded in the metal substrate.
[0068] In the metal glass composite of the embodiment, at the boundary between the metal substrate and the sprayed glass, the sprayed glass not only adheres to the metal substrate but also penetrates the metal substrate to a certain extent, forming a region where both materials are mixed. Therefore, the sprayed glass improves the adhesion strength between the two due to its penetration into the metal substrate, compared to the simple adhesion by conventional spraying. Specifically, durability can be obtained as confirmed by the ball drop height test described later.
[0069] The reason why the molten solidified portion is formed in the metal glass composite of the embodiment is believed to be due to the conditions of plasma spraying, which melts the glass material and sprays it onto the heated metal substrate. Since the molten glass material itself is at a high temperature, it is believed that the surface layer of the metal substrate is further heated by its own heating and the heat caused by the molten glass material, and metal melting occurs even in the surface layer of the metal substrate. In addition, the molten glass material collides with the surface layer of the metal substrate with the spraying force (speed, pressure) from the plasma spraying, and since both are in a molten state within a very limited range, they tend to mix with each other, and it is believed that the molten solidified portion is finally formed.
[0070] In the case of the above-mentioned Patent Document 1 (JP Patent Publication No. 2013-216977), a molten glass material penetrates into the surface of a metal substrate that has been roughened by blasting. In contrast, the metallic glass composite of the embodiment is structurally different in that a molten solidified portion is formed.
[0071] The electron microscope photographs in FIG. 3 and subsequent figures are cross-sections of prototypes of metallic glass composites, and measurements based on the photographs with increased magnification (B) in each figure confirmed that the molten solidified portion had a thickness of 0.3 μm or more. The upper limit of the molten solidified portion cannot exceed the total thickness of the sprayed glass portion. Therefore, the upper limit of the molten solidified portion is considered to be approximately 1 μm or less in thickness. As can be seen from each photograph, in the metallic glass composite of the embodiment, the boundary portion is the interface where the sprayed glass portion contacts the metal substrate portion. The molten solidified portion is a portion where the glass material is trapped and scattered within the metal substrate portion, and is the depth from the boundary portion between the metal substrate portion and the sprayed glass portion to the range where the trapped glass material is present.
[0072] The above explanation discloses the relationship between the composition and the thermal expansion coefficient of both the sprayed glass part (glass material) and the metal substrate part, and the characteristics of the molten solidified part occurring at the boundary. In addition, it is necessary to specify the state after the sprayed glass part is formed on the surface of the metal substrate part. Specifically, it is necessary to control the amount of bubbles present in the sprayed glass part. Therefore, the area ratio of bubbles of 1 μm or more in the cross section in the thickness direction of the sprayed glass part in the completed metallic glass composite is suppressed to less than 40%. When measuring the bubbles, the metallic glass composite is cut in the thickness direction of the sprayed glass part to expose the cut surface. Then, the cut surface is enlarged by a scanning electron microscope (SEM), and the area of bubbles of 1 μm or more in diameter is obtained on the exposed cut surface. Then, the total area of bubbles of 1 μm or more in diameter is calculated. The area ratio of bubbles of 1 μm or more is calculated as the total area of bubbles in the area of the cut surface of the sprayed glass part. That is, the area ratio of bubbles of 1 μm or more is calculated as "area ratio (%) of bubbles of 1 μm or more" = {(total area of bubbles of 1 μm or more on the cut surface) / (total area of the cut surface)}×100.
[0073] When the amount of bubbles increases in the sprayed glass part of the metallic glass composite, the sprayed glass part becomes so-called spongy, losing its density and reducing its structural strength. As shown in the falling ball height test described later, the higher the area ratio of bubbles in the cut surface, the lower the impact strength. Therefore, since this is an index that directly affects the durability of the metallic glass composite, the area ratio of bubbles of 1 μm or more in the cross section in the thickness direction of the sprayed glass part is less than 40%, preferably 30% or less, and more preferably 20% or less.
[0074] In addition, when the metallic glass composite is expected to be used as an electrode, if the area ratio of bubbles is high, insulation breakdown and the like will easily occur in the sprayed glass part when electricity is applied. This will cause damage to the device in which the metallic glass composite is mounted. Therefore, it is important to suppress the area ratio of bubbles as much as possible. As explained in the glass material components, when the glass material melts due to heating during spraying, the second group component (B) is likely to volatilize, and bubbles are generated by gasification at this time. In addition, during spraying, the molten glass material is instantly applied to the surface of the metal substrate and adheres to the same surface. The bubbles generated in the molten glass material cannot move, and the bubbles are cooled while remaining sealed in the sprayed glass part, remaining in the sprayed glass part.
[0075] The blending ratios of the first group component (A), the second group component (B), and the third group component (C) of the glass material are necessary to adjust the thermal expansion coefficient of the metal substrate and to control the durability of the glass quality. Therefore, the second group component (B) is blended whether one likes it or not, knowing that gasification will occur. As can be understood from this, the composition of the glass material of the embodiment is established in a balance that adjusts the thermal expansion coefficient of the metal substrate while suppressing residual bubbles from the perspective of durability.
[0076] In the metallic glass composite of the embodiment, the basic presence region and area ratio are further specified in detail. Specifically, in the boundary between the metal substrate portion and the sprayed glass portion in the longitudinal section of the metallic glass composite, it is desirable that the area ratio of bubbles of 1 μm or more existing within an area of 30% of the thickness direction of the sprayed glass portion from the boundary portion is suppressed to 50% or less. Furthermore, it is desirable that the thickness of the sprayed glass portion is in the range of 10 to 100 μm, and the area ratio of bubbles of 1 μm or more in the cross section in the thickness direction of the sprayed glass portion is less than 10% in the sprayed glass portion.
[0077] As described above, when spraying a glass material, the compositional components are vaporized and gasified by the heat of the spraying. Then, the molten glass material is sprayed before the vaporized gas diffuses, so it is left behind as bubbles. In particular, in a metal glass composite, the deep region of the sprayed glass part, in other words, the region close to the metal substrate, is unavoidably prone to having many bubbles. In addition, in order to increase the adhesive strength between the sprayed glass part and the metal substrate, it is desirable for the sprayed glass part to be dense, that is, to have as few bubbles as possible.
[0078] Therefore, in order to make it possible to grasp the form of the sprayed glass part, the area ratio of bubbles of 1 μm or more is suppressed to 50% or less, preferably 40% or less, in a region starting from the boundary and extending up to 30% (including within 30%) of the thickness direction of the sprayed glass part. By suppressing the amount of bubbles near the boundary of the sprayed glass part, the density of the sprayed glass part near the boundary increases, and the strength is easily increased.
[0079] Furthermore, the thickness of the sprayed glass part in the metallic glass composite can be adjusted by changing the amount of spraying depending on the application. However, a thicker sprayed glass part will result in an increase in glassiness, which may cause cracks after cooling and reduce durability during use. In particular, for purposes such as corrosion prevention and insulation, the thinner the thickness, the better. For this reason, the sprayed glass part is finished to a thickness in the range of 10 to 100 μm.
[0080] In a sprayed glass part of such thickness, the presence of bubbles is directly related to deterioration of performance such as durability and insulation, so it is desirable to reduce the number of bubbles even further than the above conditions. Therefore, the area ratio of bubbles of 1 μm or more in the sprayed glass part (entire cross section) is suppressed to less than 10%, preferably less than 7%. EXAMPLES
[0081] [Type of metal substrate] In producing the metallic glass composite, the following three types of metal substrate plate bodies (100 mm × 30 mm, thickness 1.2 mm) were used. SUS409, SUS430, and SS400 were used as the metal substrate parts made of body-centered cubic iron material. SUS304 was used as the metal substrate part made of face-centered cubic iron material. For reference, the metal composition (mass%) and linear expansion coefficient (×10 -6 / °C) are shown in Table 1. Since each metal in the table is an iron-based alloy, Fe is shown as the balance.
[0082] [Table 1]
[0083] [Treatment of metal substrate] The plate-shaped metal substrates shown in Table 1 were sandblasted with #60 and #80 alundum, and the surfaces were air-washed to remove dust. Prior to thermal spraying, the plate-shaped bodies were heated to about 700 to 1000°C in an electric furnace, and thermal spraying was performed under the conditions described below before the temperature was lowered.
[0084] [Glass material composition] The components were mixed according to the composition in Table 2 below to prepare glass materials of prototypes 1 to 16, which were then pulverized into frit (powder). The frit was classified to the desired average particle size. In the table, each component is shown as mass % of the entire glass material. For ease of understanding, the total of the second group components (B) and the total of the third group components (C) in the entire glass material are also shown. In addition, the linear expansion coefficient (α) (unit: × 10 -6 / ℃).
[0085] [Table 2]
[0086] [Thermal spraying equipment and conditions] For the plasma spraying, the spraying equipment used was Praxair Technology, Inc.'s Model SG-100 Plasma Spray Gun. In addition, the equipment used to control the supply of electricity, cooling water, gas, and spraying material was Praxair's Model 3710 Plasma Control Console, the equipment used to supply glass material was Praxair's Model 1264 Powder Feeder, the power supply was Praxair's Model PS-1000 Plasma Power Source, and the high frequency generator was Praxair's Model HF-2200.
[0087] The spraying was performed in common with the frit of the glass material of prototypes 1 to 16. However, the scanning speed of the plate-shaped metal substrate during spraying was increased or decreased to adjust the amount of deposition caused by spraying onto the surface. Thermal spraying conditions Voltage: 30~50V Current: 700~1000A Metallic base heating temperature: 700-1000℃
[0088] For each of the thermal spraying conditions, if the lower limit is exceeded, the effect of insufficient heat is so great that the glass material does not melt on the surface of the metal substrate, and adhesion cannot be ensured, whereas if the upper limit is exceeded, the melting of the metal substrate becomes too intense, causing deformation of the shape of the metal substrate itself.
[0089] The raw material supply conditions were the following gas species and flow rates. The raw material carrier gas was dry air or argon. When the flow rate is Fa (NL / min) and the raw material supply rate is Fb (g / min), "Fb / Fa" was controlled to 0.4 or less. If "Fb / Fa" exceeds 0.4, melting of the base material becomes difficult even if the above-mentioned thermal spraying conditions are satisfied.
[0090] [Characteristics of metallic glass composites] Prototype samples G1 to G21 were fabricated as metallic glass composites having a metal substrate made of body-centered cubic iron material, and prototype samples H1 to H8 were fabricated as metallic glass composites having a metal substrate made of face-centered cubic iron material. The results of prototype samples G1 to G21 are shown in Table 3, and the results of prototype samples H1 to H8 are shown in Table 4.
[0091] Tables 3 and 4 list, in order, the prototype number, the type of glass material disclosed in Table 2, the type of metal substrate, the heating temperature (°C) of the metal substrate, the amount of current during spraying (A), the thickness (μm) of the sprayed glass portion of the final metallic glass composite, the area ratio (%) of bubbles 1 μm or larger in the entire sprayed glass portion, the area ratio (%) of bubbles 1 μm or larger present in a region within 30% of the thickness of the sprayed glass portion starting from the boundary, the thickness of the molten and solidified portion (μm), the maximum diameter (μm) of the bubbles present in the sprayed glass portion, the ball drop height (cm), and the dielectric strength test (MV / m).
[0092] To observe and measure the thickness and bubbles, the metallic glass composites of each prototype were cut vertically and observed with a scanning electron microscope (SEM). Figure 3 shows electron microscope photographs of prototype G1, Figure 4 shows prototype G2, Figure 5 shows prototype G6, Figure 6 shows prototype G11, Figure 7 shows prototype G13, Figure 8 shows prototype G19, and Figure 9 shows prototype H5. (A) in each figure is a 100x magnified photograph, and (B) in each figure is a 1000x magnified photograph.
[0093] The falling ball height was evaluated by freely dropping a 150g steel ball from directly above onto the sprayed glass part (exposed glass surface) of the metallic glass composite of each prototype. The height (vertical length from the sprayed glass part to the steel ball) at which the impact of the dropped steel ball caused visible abnormalities in the sprayed glass part, such as fissures, cracks, or chips, was recorded as the falling ball height for that prototype. The plot graph (scatter diagram) in Figure 10 shows the relationship between the total bubble area ratio (%) in the sprayed glass part of the metallic glass composite of each prototype and the falling ball height (cm).
[0094] The dielectric strength test was conducted in accordance with the test method of JIS C 2110 (2016) (IEC 60243-1:2013), and the metallic glass composite of each prototype was measured. The plot graph (scattering diagram) in Figure 11 shows the relationship between the bubble area ratio (%) at the boundary of the sprayed glass part of the metallic glass composite of each prototype and the dielectric strength (MV / m). For the dielectric strength test, a Nippon Technart model HP-5110DS was used, and the presence or absence of leakage was evaluated by applying 10kV for 1 minute.
[0095] For the metallic glass composites of prototypes G1 to G19 in Table 3, the moving speed of the spraying device was 31 mm / sec, prototypes G1 to G18 were sprayed five times on the metal substrate, and prototype G19 was sprayed once. For prototype G20, the moving speed of the spraying device was 52 mm / sec, and the spraying was performed once. For prototype G21, the moving speed of the spraying device was 125 mm / sec, and the spraying was performed once.
[0096] For the metallic glass composites of Samples H1 to H8 in Table 4, the moving speed of the thermal spraying device was set to 31 mm / sec, and the metal substrate was thermally sprayed five times.
[0097] For the metallic glass composites of prototype examples H9 to H16 in Table 5, the movement speed of the spraying device was 125 mm / sec and the metal substrate was sprayed once; for the metallic glass composites of prototype examples H17 to H21, the movement speed of the spraying device was 52 mm / sec and the metal substrate was sprayed once; and for the metallic glass composites of prototype examples H22 to H24, the movement speed of the spraying device was 31 mm / sec and the metal substrate was sprayed five times.
[0098] [Table 3]
[0099] [Table 4]
[0100] [Table 5]
[0101] [Results and Discussion] From Table 3, the metallic glass composite of prototype G6 used the glass material of prototype 4. In prototype 4, the proportion of the second group component (B), which is a volatile component, was high (total 32 mass%). As a result, the area ratio of bubbles increased. The ball drop height worsened due to an increase in voids caused by an increase in bubbles. In contrast, the metallic glass composite of prototype G5 used the glass material of prototype 3. The proportion of the second group component (B) in the glass material of prototype 3 was 29 mass% in total. As a result, a decrease in bubbles was confirmed in the total bubble area ratio of prototype G5, and an increase in the ball drop height was also evident. Therefore, for the metal substrate portion made of a body-centered cubic iron material found in SUS409, the upper limit of the proportion of the second group component (B) is estimated to be 30 mass%.
[0102] The metallic glass composites of prototypes G19 to G21 are examples in which the glass film thickness of the sprayed glass portion was thinned to 100 μm or less. For prototypes G19 to G21, the glass materials of prototypes 1 and 16, which have a low ratio of the second group component (B), were used. This is thought to have suppressed the amount of volatilization during spraying and reduced the generation of bubbles. The results of the ball drop height confirmed the formation of an extremely strong sprayed glass portion.
[0103] When preparing the metallic glass composites of each prototype, the spraying environment using the plasma spraying device is in a temperature range that melts the outermost surface of the metal substrate that serves as the base for spraying. Therefore, the composition components of the glass material are more likely to volatilize due to the influence of heat during spraying. In particular, the linear expansion coefficient of body-centered cubic iron material is lower than that of metals made of face-centered cubic iron material, so it is more important to control the thermal expansion rate (linear expansion coefficient) and to suppress the upper limit of the second group component (B), which is easily volatilized. Therefore, based on the results of the prototypes, the blending ratio of the second group component (B) in the glass material is 10 to 30 mass%, preferably 20 to 30 mass%.
[0104] The metallic glass composites of prototypes H1 to H24 are examples of a metal substrate (SUS304) made of face-centered cubic iron material. In the case of face-centered cubic iron material, the linear expansion coefficient is larger than that of body-centered cubic iron material, so the restrictions on the blending ratio of the second group component (B) are relaxed. In addition, the amount of air bubbles is generally small, and the falling ball height is good. For this reason, the blending ratio of the second group component (B) in the glass material is 25 to 35 mass%.
[0105] When preparing the glass material of the prototype example, if the SiO2 content of the first group component (A) in the glass material exceeds 70% by mass, the viscosity of the molten glass material during thermal spraying becomes excessive, and the residual bubbles become significant. Also, if it is less than 35% by mass, it becomes difficult to adjust the linear expansion coefficient. Therefore, in the case of a body-centered cubic iron material, the SiO2 content of the first group component (A) in the glass material is 35 to 70% by mass. For the same reason, in the case of a face-centered cubic iron material, the SiO2 content of the first group component (A) in the glass material is 50 to 60% by mass.
[0106] The third group component (C) is a component that affects the viscosity of the glass material in a molten state. From the results of the glass material and metallic glass composite of each prototype, in the case of iron material with a body-centered cubic crystal system, the total amount of the third group component (C) in the glass material is 10 to 30 mass%, and in the case of iron material with a face-centered cubic crystal system, the amount of SiO2 of the first group component (A) in the glass material is 10 to 20 mass%.
[0107] Considering the results of the falling ball height and dielectric strength of the metallic glass composites of prototypes G1 to G19 and the metallic glass composites of prototypes H1 to G24, the area ratio of bubbles of 1 μm or more in the cross section in the thickness direction of the sprayed glass part is less than 40%, preferably 30% or less. In addition, the area ratio of bubbles of 1 μm or more existing in an area within 30% of the thickness direction of the sprayed glass part from the boundary part is also preferably 50% or less. Furthermore, in the metallic glass composites of prototypes G19 to G21 where the thickness of the sprayed glass part is 100 μm or less, the area ratio of bubbles of 1 μm or more existing in the thickness direction of the sprayed glass part can be extremely reduced to 10% or less, resulting in improved performance in the falling ball height and dielectric strength.
[0108] The relationship between the total bubble area ratio (%) and the falling ball height (cm) is shown as a plot graph in Figure 10. As the total bubble area ratio increases, the value of the falling ball height tends to decrease. This indicates a decrease in the strength of the sprayed glass part due to the increase in bubbles. The relationship between the bubble area ratio (%) at the boundary and the dielectric strength (MV / m) is shown as a plot graph in Figure 11. Dielectric strength is maintained so long as the bubble area ratio at the boundary is up to 40%. However, once the bubble area ratio at the boundary exceeds 40%, the decrease in dielectric strength becomes noticeable. From this trend, the range of the bubble area ratio mentioned above is determined. [Explanation of symbols]
[0109] 1A, 1B, 1C, 1D Metallic glass composite 10,11,12,13,14 Metal base material part 20. Thermal Spray Glass Section 21 Bubbles 22 Residual glass 30 Boundary 40 Melted and solidified part T30 30% of the thickness of the sprayed glass
Claims
1. A metal substrate made of a body-centered cubic iron material and a sprayed glass portion formed on the metal substrate with a film thickness of 10 to 2000 μm, The glass material forming the sprayed glass portion is As the first group component (A), SiO 2 : 35 to 70% by mass, As the second group component (B), B 2 O 3 : 9 to 15% by mass, Li 2 O: 5 to 9% by mass; Na 2 O: 4 to 10% by mass, the total of which is 18 to 30% by mass, As the third group component (C), BaO: 0 to 15% by mass; TiO 2 : 2 to 15% by mass, A 2 O 3 : 0 to 8% by mass, ZnO: 0 to 15% by mass, the total of which is 10 to 30% by mass, The total amount of the first group component (A), the second group component (B), and the third group component (A) constitutes 90% by mass or more of a main component (D), The linear expansion coefficient of the glass material at room temperature to 300° C. is 9 to 11 (×10 6 / °C), The area ratio of bubbles having a size of 1 μm or more in a cross section in the thickness direction of the sprayed glass portion is less than 40%.
1. A metallic glass composite comprising:
2. A metal substrate made of a face-centered cubic iron material and a sprayed glass portion formed on the metal substrate with a thickness of 10 to 2000 μm, The glass material forming the sprayed glass portion is As the first group component (A), SiO 2 : 50 to 60% by mass, As the second group component (B), B 2 O 3 : 2 to 8 mass%; Li 2 O: 8 to 15% by mass; Na 2 O: 8 to 20% by mass, the total of which is 25 to 35% by mass, As the third group component (C), BaO: 3 to 12 mass%; TiO 2 : 4 to 15% by mass, A 2 O 3 : 0 to 5% by mass, ZnO: 0 to 5% by mass, the total of which is 10 to 20% by mass, The total amount of the first group component (A), the second group component (B), and the third group component (A) constitutes 90% by mass or more of a main component (D), The linear expansion coefficient of the glass material at room temperature to 300° C. is 14 to 17 (×10 6 / °C), The area ratio of bubbles having a size of 1 μm or more in a cross section in the thickness direction of the sprayed glass portion is less than 40%.
1. A metallic glass composite comprising:
3. 3. The metallic glass composite according to claim 1, wherein a difference between the linear expansion coefficient of the glass material and the linear expansion coefficient of the metal substrate is within 15%.
4. The metallic glass composite according to claim 1 or 2, further comprising a molten solidified portion in which the sprayed glass portion is embedded in the metal substrate at a boundary between the metal substrate and the sprayed glass portion in the cross section, and the molten solidified portion has a thickness of 0.3 μm or more.
5. 3. The metal glass composite according to claim 1, wherein the area ratio of bubbles having a size of 1 μm or more that are present within an area of 30% or less in a thickness direction of the sprayed glass portion from a boundary between the metal substrate portion and the sprayed glass portion in the cross section is 50% or less.
6. 3. The metallic glass composite according to claim 1, wherein the sprayed glass portion has a thickness of 10 to 100 μm, and the area ratio of bubbles having a size of 1 μm or more in a cross section in the thickness direction of the sprayed glass portion is less than 10%.
7. The component other than the main component (D) of the glass material is an auxiliary component (E), The auxiliary component (E) is CaO, SrO, MgO, P 2 O 5 , K 2 O.V. 2 O 5 , Cr 2 O 3 , MnO 2 , Fe 2 O 3 , Co 3 O 4 , NiO 2 , CuO, Y 2 O 3 , ZrO 2 , Nb 2 O 2 , MoO 3 , SnO 2 , Sb 2 O 3 , W.O. 3 , PbO, Bi 2 O 3 , La 2 O 3 , CeO 2 , P 6 O 11 , Nd 2 O 3 , Sm 2 O 3 , Gd 2 O 3 3. The metallic glass composite according to claim 1, wherein the metallic glass composite is made of one or more of the following:
Citation Information
Patent Citations
Frit for glass flame spraying
JP1989122937A
Formation of glass film
JP1991180457A
Formation of glass coating film
JP1993221685A
Soluble vitreous material thermal spraying-coated member and its production
JP1999080922A
Method for manufacturing roll body having glassy film formed thereon, glassy thermal spray material used for the same, and silent discharge electrode for ozone-generating device according to the manufacturing method
JP2009221540A